Incidence of post-procedure symptomatic urinary tract infection in children undergoing micturition cystourethrogram in the absence of antibiotic cover - Suresh Kumar Thanneeru; Avinash Sriramapura Ravindra; Ann Sumin Toms; Tarun John Jacob; Jujju Jacob Kurian (SpringerOpen, 2022)
Abstract Context Prophylactic antibiotics are usually not recommended for an in and out catheterization. However procedures involving similar catheterizations like micturition cystourethrogram (MCUG) and cystometrogram are being performed under prophylactic antibiotic cover. Aims We aim to find the incidence of symptomatic urinary tract infections following MCUG done in children without antibiotic cover. Settings and design A retrospective cross sectional study was conducted on 398 patients who underwent MCUG from January 2015 to January 2016. The median age was 24 months and here were 272 males and 126 females, with 102 of them being infants. Methods and material Urine microscopy or culture was checked before performing the MCUG and only those without UTI were included in the study. Those with symptomatic and culture proven UTI within 2 weeks post-MCUG were defined as having post-procedure UTI (ppUTI). The incidence of post-procedure UTI was calculated and was compared with other studies. Statistical analysis used Data was entered in Microsoft Excel and analyzed using SPSS. Categorical variables were summarized as percentage and continuous variables were summarized as mean with standard deviation. Results Symptomatic procedure induced UTI were seen in only 3 of the 398 (0.75%) patients with a 95% CI of 0.02-0.008. Conclusions Strict adherence to aseptic precautions while performing an MCUG and prompt initiation of appropriate therapy when indicated may help obviate the need for routine administration of pre procedure antibiotics before MCUG.